#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# A spring balance hanging in steady state inside a lift accelerating upwards shows a reading of double the actual mass of an object. Then the acceleration of the lift is-(a)    √5g(b)    2g(c)     g(d)    √3g              pls explain!!!!

shubham pansare
15 Points
10 years ago

initially,, kx=mg   -(1)

2kx=m(g+a)

2mg=m(g+a)....use (1)

therefore a=g.

509 Points
10 years ago

when lift acclerates it upward direction then ,then particle experinces a seudo force in downward direction

magnitude of this force = ma                     (a is accleration of lift)

net force in downward direction = net weight

weight = m(g+a)

weight is given 2mg so

2mg = m(g+a)

a = g

Fawz Naim
37 Points
10 years ago

as the lift is accelerating upwards a pseudo force is acting on the mass hanging from the spring balance.

let the acc of the lift be a    and the mass of the body be m

so the total downward force acting on the object =weightof the object+pseudo force(ma)

F=mg+ma

now the spring balance is showing the mass of the object which is double its actual mass

so  F=2mg

mg+ma=2mg

ma=mg

a=g